Odpowiedzi

  • Użytkownik Zadane
2009-06-04T20:15:43+02:00
A)z/a=t/c //*a
z=at/c
b)b/z=4x/a //*z
b=4xz/a //*a
ab=4xz//:4x
z=ab/4x
c)x=a+b/z //*z
xz=a+b //:x
z=a+b/x
d)z²a=c//:a
z²=c/a
z=√c:√a
e)z/a=b/z //*az
z²=ab
z=√ab
f)z²+1/c=b/3 //*c
z²+1=bc/2
z²=bc/3-1
z=√bc:√3-√1

2009-06-04T20:17:24+02:00
A)
z/a = 1/c
zc=a /:c
z=a/c

b)
b/z=4x/d
4xz = bd
z=bd/4x

c)
x=a+b/z / *z
zx=a+b / :x
z=(a+b)/x

d)
z do kwadraru * a = c / :a
z do kwadraru = c/a
z= pierwiastek z c/a

e)
z/a = b/z
z do kwadratu = ab
z= pierwiastek z ab

f)
(z do kwadraru + 1) / c = b/3
3(z do kwadraru + 1) = bc
3 z do kwadratu + 3 = bc
3 z do kwadraru = bc - 3
z do kwadraru = (bc - 3) / 3
z= pierwiastek z (bc - 3) / 3
2009-06-04T20:23:17+02:00
A) z/a = t/c /*a
z= ta/c

b) b/z = 4x/d /*z
b=4xz/d /*d
bd=4xz /:4x
bd/4x =z

c)x=a+b/z /*z
zx=a+b
z=a+b/x

d)z(do 2)a=c /pierw.
pier. z(do2)a = c
za=c
z=c/a

e) z/a = b/z /*a
z= ab/z /:z
z(do2) = ab /pierw.
z= pierw. ab

f) z(do3)+1/c = b/3 /*c
z(do3) +1=bc/3
z(do3)=bc/3 -1 / pierw.3stopnia
z= pierw. bc/3 - 1